Amidyl Radical Directed Remote Allylation of Unactivated sp3 C−H Bonds by Organic Photoredox Catalysis. (11th January 2019) - Wu, Kui; Wang, Lushun; Colón‐Rodríguez, Sonivette; Flechsig, Gerd‐Uwe; Wang, Ting
Abstract: The development of visible‐light‐mediated allylation of unactivated sp 3 C−H bonds is reported. The remote allylation was directed by the amidyl radical, which was generated by photocatalytic fragmentation of a pre‐functionalized amide precursor. Both aromatic and aliphatic amide derivatives could successfully deliver the remote C−H allylation products in good yields. A variety of electron deficient allyl sulfone systems could be used as δ‐carbon radical acceptor. Abstract : Sichtbares Licht vermittelt die Allylierung nichtaktivierter C(sp 3 )‐H‐Bindungen in entfernter Position. Dabei wird zunächst ein Amidylradikal durch photokatalytische Fragmentierung einer funktionalisierten Amidvorstufe erzeugt. Aromatische und aliphatische Amidderivate ergaben die C‐H‐Allylierungsprodukte in guten Ausbeuten. Verschiedene elektronenarme Allylsulfonsysteme dienten als δ‐Kohlenstoff‐Radikalakzeptoren.